Transitório ou permanente: a clínica psicanalítica diante da relação entre a temporalidade e o esvaziamento do ser - Peres, Kenia (2017)
The psychoanalytic clinic is now faced with the effects of new psychic realities. The so-called contemporary psychoanalysis, characterized mainly by the breakdown of the theoretical rigidity of the post-Freudian psychoanalytic schools, seeks ways of understanding and new clinical and theoretical positions, in the face of what André Green called non-neurotic structures. This thesis presents the work with patients who arrive at the psychological offices showing common traits among these pictures, which distinguish them from the others, since these patients describe their evils through a distanced speech, without implication, emptied of emotion, without relief, in a thread monotonous. Such patients, considered subjects with symbolic deficits, still have the question of acceleration of time, as an aggravating factor for their condition of being emptied of meaning. For this, the are essential